Islamic Banking Synergity As Halal Industry Development In Indonesia - Rahmayati Rahmayati (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to determine how the halal industry in Indonesia can develop through the role of Islamic banking with financing channeled by Islamic banks to financing customers. The methodusedinthisresearchisqualitativeresearch.Qualitativedataprocessingtechniquessourced from the analysis of interviews that have been conducted by Islamic banks and financing customers. The results of this study prove that Islamic banking can encourage the increase and developmentofthehalalindustrysectorthroughfinancingcustomersinIslamicbanks.Thisstudy usestworesearchdirectionstoachievetheobjectivesoftheroleofIslamicbankingindeveloping the halal industry through its strategies and policies to help improve the halal industry by socializing the halal industry to the public and specifically to sharia bank customers who will proposefinancing.